Longitudinal development of pain sensitivity in adolescent non-suicidal self-injury. (June 2017) - Koenig, Julian; Rinnewitz, Lena; Niederbäumer, Maren; Strozyk, Tabea; Parzer, Peter; Resch, Franz; Kaess, Michael
Abstract: Nonsuicidal self-injury (NSSI) is associated with reduced pain sensitivity (PS). Existing theories posit that altered PS is a risk factor for NSSI. Cross-sectional data suggest that PS normalizes in those terminating self-injury. However, previously no study addressed the longitudinal course of PS in patients engaging in NSSI. We addressed changes in PS and clinical symptomatology in adolescents with NSSI (n = 18) and matched controls (n = 19) over one year. Despite significant clinical improvements, PS did not change in the NSSI group but decreased in controls. Greater NSSI reduction was associated with increased pain tolerance. Findings are discussed in the light of current theories on PS in NSSI. Highlights: Nonsuicidal self-injury (NSSI) is associated with reduced pain sensitivity (PS). Cross-sectional studies suggest a normalization of PS in individuals with remission of NSSI. This is the first study addressing longitudinal changes in PS in patients with NSSI. Results provide evidence for an inverse relationship between clinical improvements and changes in PS. NSSI may be terminated once pain tolerance gets too high.